The Mother Herb: Plant Storywork, Grief & More-Than-Human Care in Compromised Times - Perdibon, Anna; McSherry, Alice (Journal of Ecohumanism, 2023)
Herbalists and plants have healing relationships that shape cultures throughout collapse and regeneration. Indeed, the herbalist was once a highly esteemed role in communities, working-with plants to facilitate relational care and healing of human and non-human kin alike. This article explores the ethics of mothering and kinship, as experienced through the lens of a herbalist, by disrupting standardized notions of mothering as a human-to-human biological reality and embracing an understanding of mothering as an interspecies and multi-generational practice. To do so, we engage in an animist and ecofeminist auto-ethnographic process of thinking-with Mugwort (Artemisia Vulgaris) to re-story our own relationships with mothering without biologically being mothers and how this shapes our relationships with grief, loss, and love in contemporary times. We look to Mugwort as an important ancestral ‘plant mother’ in each of our cultural lineages and draw on herbal folklore and practices to think through the complexities of more-than-human care. We argue that mothering is a subjective and contextual practice of kin-making, and how herbalists have ritually engaged in this since time immemorial. Herbalism can thus be framed as an ecological praxis that takes seriously multispecies mothering and gestures toward future(s) where mutual flourishing can be enacted in plural forms.